Cathelicidin treatment silences epithelial-mesenchymal transition involved in pulmonary fibrosis in a murine model of hypersensitivity pneumonitis - Lemieszek, Marta Kinga; Golec, Marcin; Zwoliński, Jacek; Dutkiewicz, Jacek; Milanowski, Janusz (International journal of molecular sciences, 2022)
Pulmonary fibrosis is becoming an increasingly common pathology worldwide. Unfortunately, this disorder is characterized by a bad prognosis: no treatment is known, and the survival rate is dramatically low. One of the most frequent reasons for pulmonary fibrosis is hypersensitivity pneumonitis (HP). As the main mechanism of pulmonary fibrosis is a pathology of the repair of wounded pulmonary epithelium with a pivotal role in epithelial-mesenchymal transition (EMT), we assumed that EMT silencing could prevent disease development. Because of several biological features including wound healing promotion, an ideal candidate for use in the treatment of pulmonary fibrosis seems to be cathelicidin. The aim of the studies was to understand the influence of cathelicidin on the EMT process occurring during lung fibrosis development in the course of HP. Cathelicidin’s impact on EMT was examined in a murine model of HP, wherein lung fibrosis was induced by chronic exposure to extract of Pantoea agglomerans (SE-PA) by real-time PCR and Western blotting. Studies revealed that mouse exposure to cathelicidin did not cause any side changes in the expression of investigated genes/proteins. Simultaneously, cathelicidin administered together or after SE-PA decreased the elevated level of myofibroblast markers (Acta2/α-smooth muscle actin, Cdh2/N-cadherin, Fn1/Fibronectin, Vim/vimentin) and increased the lowered level of epithelial markers (Cdh1/E-cadherin, Ocln/occludin). Cathelicidin provided with SE-PA or after cessation of SE-PA inhalations reduced the expression of EMT-associated factors (Ctnnd1/β-catenin, Nfkb1/NFκB, Snail1/Snail, Tgfb1/TGFβ1 Zeb1/ZEB1, Zeb2/ZEB2) elevated by P. agglomerans. Cathelicidin’s beneficial impact on the expression of genes/proteins involved in EMT was observed during and after the HP development; however, cathelicidin was not able to completely neutralize the negative changes. Nevertheless, significant EMT silencing in response to cathelicidin suggested the possibility of its use in the prevention/treatment of pulmonary fibrosis.